Pneumococcal Surface Protein A-Hybrid Nanoparticles Protect Mice from Lethal Challenge after Mucosal Immunization Targeting the Lungs - Douglas Borges de Figueiredo; Kan Kaneko; Tasson da Costa Rodrigues; Ronan MacLoughlin; Eliane Namie Miyaji; Imran Saleem; Viviane Maimoni Gonçalves (MDPI AG, 2022)
Pneumococcal disease remains a global burden, with current conjugated vaccines offering protection against the common serotype strains. However, there are over 100 serotype strains, and serotype replacement is now being observed, which reduces the effectiveness of the current vaccines. Pneumococcal surface protein A (PspA) has been investigated as a candidate for new serotype-independent pneumococcal vaccines, but requires adjuvants and/or delivery systems to improve protection. Polymeric nanoparticles (NPs) are biocompatible and, besides the antigen, can incorporate mucoadhesive and adjuvant substances such as chitosans, which improve antigen presentation at mucosal surfaces. This work aimed to define the optimal NP formulation to deliver PspA into the lungs and protect mice against lethal challenge. We prepared poly(glycerol-adipate-co-ω-pentadecalactone) (PGA-co-PDL) and poly(lactic-co-glycolic acid) (PLGA) NPs using an emulsion/solvent evaporation method, incorporating chitosan hydrochloride (HCl-CS) or carboxymethyl chitosan (CM-CS) as hybrid NPs with encapsulated or adsorbed PspA. We investigated the physicochemical properties of NPs, together with the PspA integrity and biological activity. Furthermore, their ability to activate dendritic cells in vitro was evaluated, followed by mucosal immunization targeting mouse lungs. PGA-co-PDL/HCl-CS (291 nm) or CM-CS (281 nm) NPs produced smaller sizes compared to PLGA/HCl-CS (310 nm) or CM-CS (299 nm) NPs. Moreover, NPs formulated with HCl-CS possessed a positive charge (PGA-co-PDL +17 mV, PLGA + 13 mV) compared to those formulated with CM-CS (PGA-co-PDL −20 mV, PLGA −40 mV). PspA released from NPs formulated with HCl-CS preserved the integrity and biological activity, but CM-CS affected PspA binding to lactoferrin and antibody recognition. PspA adsorbed in PGA-co-PDL/HCl-CS NPs stimulated CD80+ and CD86+ cells, but this was lower compared to when PspA was encapsulated in PLGA/HCl-CS NPs, which also stimulated CD40+ and MHC II (I-A/I-E)+ cells. Despite no differences in IgG being observed between immunized animals, PGA-co-PDL/HCl-CS/adsorbed-PspA protected 83% of mice after lethal pneumococcal challenge, while 100% of mice immunized with PLGA/HCl-CS/encapsulated-PspA were protected. Therefore, this formulation is a promising vaccine strategy, which has beneficial properties for mucosal immunization and could potentially provide serotype-independent protection.